Propuesta de test para evaluar la capacidad aeróbica en triatletas juveniles - García, P. F.; Vázquez, L. Á. G.; López-Calleja, M. A. R. (PODIUM: Journal of Science and Technology in Physical Culture, 2023)
Today's sport motivates the search for new solutions that allow the athlete to respond to high physical demands within a sustainable sport. One solution is to search for tests for performance monitoring. The aim of this study is to propose a field test for the evaluation of aerobic capacity, carrying out a triathlon with lower values in terms of distance and duration with respect to the sprint triathlon. The study presents a field test proposal for the evaluation of aerobic capacity performing triathlons with shorter distances. The distance was determined through a practical study of competitive activity. In the validation, the test was applied to 12 athletes of the youth category with an average age of 16.3 years (± 1,3). The content validity was verified using the criteria of 12 specialists who stated that it adequately represents the aerobic capacity. Reliability and concordance were checked using the Wilcoxon rank test where asymptotic significance was 0.574. By the equivalence criterion, the test was monitored by comparing heart rate values with those of a simulated sprint triathlon. For the contrasted validity, the results of the triathletes were compared with those of five swimmers, three cyclists and two long-distance runners. The test times were lower in the triathletes, confirming that the test is specific for triathletes.